Nanofibrous Scaffolds Containing Hydroxyapatite and Microfluidic-Prepared Polyamidoamin/BMP-2 Plasmid Dendriplexes for Bone Tissue Engineering Applications - Doosti-Telgerd M (Dove Medical Press, 2020)
Mehdi Doosti-Telgerd,1 Fatemeh Sadat Mahdavi,2 Farzad Moradikhah,3 Mohammad Porgham Daryasari,1 Rahimeh Bayrami Atashgah,1 Banafsheh Dolatyar,4 Hamid Akbari Javar,5 Ehsan Seyedjafari,2 Iman Shabani,3 Ehsan Arefian,6 Farhood Najafi,7 Yaser Abdi,8 Mohsen Amini9 1Department of Pharmaceutical Biomaterials, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Biotechnology, University of Tehran, Tehran, Iran; 3Department of Biomedical Engineering, Amirkabir University of Technology, Tehran, Iran; 4Department of Cell and Developmental Biology, School of Biological Sciences, College of Science, University of Tehran, Tehran, Iran; 5Department of Pharmaceutics, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 6Department of Microbiology, School of Biology, College of Science, University of Tehran, Tehran, Iran; 7Department of Resin and Additives, Institute for Color Science and Technology, Tehran, Iran; 8Department of Physics, University of Tehran, Tehran, Iran; 9Department of Medicinal Chemistry, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, IranCorrespondence: Hamid Akbari JavarDepartment of Pharmaceutics, Faculty of Pharmacy, Tehran University of Medical Sciences, P.O. Box: 1417614411, Tehran, IranTel +98 2164122205Email akbarijo@tums.ac.irObjective: The aim of this study is to fabricate functional scaffolds to gene delivery bone morphogenetic protein-2 (BMP-2) plasmid for bone formation in bone tissue engineering.Methods: Dendriplexes (DPs) of generation 4 polyamidoamin (G4-PAMAM)/BMP-2 plasmid were prepared through microfluidic (MF) platform. The physiochemical properties and toxicity of DPs were evaluated by DLS, AFM, FESEM and MTT assay. In order to create a suitable environment for stem cell growth and differentiation, poly-l-lactic acid (PLLA) and poly-l-lactic acid/poly (ethylene oxide) (PLLA/PEO) scaffolds containing hydroxyapatite nanoparticles (HA) and DPs were fabricated by the electrospinning method. The osteogenic potency of the scaffolds on human adipose tissue-derived mesenchymal stem cells (hASCs) was investigated.Results: The results revealed that tuning the physical properties of DPs by adjusting flow parameters in microfluidic platform can easily improve the cell viability compared to conventional bulk mixing method. Also, the result showed that the presence of HA and DPs in PLLA/PEO scaffold enhanced alkaline phosphatase (ALP) activity and increased the amount of deposited Ca, as well as, related to osteogenesis gen markers.Conclusion: This study indicated that on using the MF platform in preparation of DPs and loading them along with HA in PLLA/PEO scaffold, the osteogenic differentiation of hASCs could be tuned.Keywords: microfluidic, dendriplex, nanofibrous scaffolds, bone tissue engineering